(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Education is continually changing, and new technological advancement can affect many ventures, particularly in advancing teaching methodologies. The Philippines is considered a home to many immigrants, which is reflected in its wide variety of Foreign Languages. With the rapid growth and availability of technology, language is incorporating different additional aids to learn the language with the help of Multimedia to make their task easier and more dynamic. According to Webster’s Dictionary, Multimedia is defined as training or educational materials directed at both the senses of hearing and the sense of sight, films, recordings, photographs, and GIFs that are used in classroom instruction. Multimedia is one of the most common needs in our education program, which is used in the classroom to encourage learning and make a process to make it easier and more interesting. Multimedia is the best device for making an effective way of learning process and the best tool for the dissemination of knowledge in one classroom. The goal of Multimedia is to enhance strategies and to help students understand the lesson easily. Multimedia no doubt reflects that technical devices have a greater impact and dynamic, informative systems. The researchers included the purpose, role, and benefits of 21st-century learning before introducing multimedia when using multimedia in a foreign language, which is the main focus of the study. The researchers find it appropriate to utilize the descriptive method in line with the concerned research on digital presentation with multimedia in foreign languages and its Implications for useful learning. The findings of the data show that video presentation has the highest mean value in the descriptive scale, which is the most useful compared to the other types of multimedia in learning a foreign language. The researchers discovered that respondents find multimedia to be extremely useful in learning a foreign language, particularly in terms of expanding and developing their vocabulary.